The Study of the Problems in Teaching Practicum of Chinese Major Students at the Faculty of Humanities and Social Sciences, Nakhon Pathom Rajabhat University - Pankitwanitjalearn, Natrudee; Wanla, Wipawee; Sripoka, Araya (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2025)
The purpose of this research was to study the problems in teaching practicum of chinese major students at the faculty of humanities and social sciences, Nakhon pathom rajabhat university, first semester of the academic year 2023. The research sample was 30 Chinese major Students and 10 tutors, which was obtained by means of purposive sampling. The research instruments was a three-part questionnaire. Part One was the demographic data of the research sample. Part Two was a rating scale questionnaire eliciting problems related to field experience in the teaching practicum of major Students. Part Three concerned other opinions regarding field experience in the teaching practicum. The research finding showed that: 1) Students practicing teaching professional gave the opinion that the problems in professional teaching practicum were found to be at a high level, namely : Textbooks (x ̅= 3.67), teaching aids x ̅= 3.70) and homework submissions (x ̅= 4.27). In addition, many educational institutions lack Chinese textbooks. and budget to support Chinese language teaching and learning. 2) The mentor teacher reported that there were problems to be at a high level, namely: teaching aids (x ̅= 3.60) and learning management (x ̅= 3.50). This is because interns mainly use textbooks and Microsoft PowerPoint to organize teaching, emphasizing lectures and lacking interesting teaching aids and interesting teaching activities. There will also be pronunciation errors and grammatical errors. But in terms of self-control, students are volunteers and actively participate in various school activities and work.